Pengaruh Desain Konten dan Interaksi Komunitas Menumbuhkan Loyalitas Pemain Mobile Legends melalui Player Engagement di Kota Denpasar - Made Bagus Dwi Permana; I Wayan Joniarta (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid growth of the mobile gaming industry in Indonesia has increased competition among MOBA games, making player retention a major challenge. Many players switch to competing titles due to content fatigue and limited social interaction. This study aims to analyze the effects of content design and community interaction on player engagement and player loyalty among Mobile Legends: Bang Bang users in Denpasar City. Using a purposive sampling approach, data were collected from 180 active players through a structured questionnaire and analyzed with SmartPLS 4. The findings show that both content design and community interaction significantly enhance player engagement, which in turn positively influences player loyalty. Content design and community interaction also exhibit direct positive effects on loyalty. Furthermore, player engagement is found to mediate the relationship between each independent variable and player loyalty. These results highlight the importance of innovative content and supportive community environments in strengthening long-term player commitment.